95 Interdisciplinary learning on a postgraduate genomic medicine course – help or hindrance?. (22nd November 2019) - Garrett, Alice
Abstract : Background: Genomics is becoming increasingly relevant to the NHS workforce, particularly those caring for complex paediatric patients, many of whom have a genomic diagnosis. Knowledge gaps amongst staff have limited the uptake of genomics in mainstream healthcare. To help address this, Health Education England (HEE) has funded places for NHS staff on a Genomic Medicine MSc course with a national curriculum, delivered at multiple Higher Educational institutions. Study aim: To explore the experiences of interdisciplinary learning (i.e. the involvement of two or more disciplines that share information and decisions) of course participants. Methods: Participants on the 'Molecular Pathology of Cancer and Application in Diagnosis, Screening and Treatment' module of the Genomic Medicine MSc course were invited to complete an anonymous online questionnaire on their experiences of interdisciplinary learning on the module. Questionnaire responses informed the questions for follow-up semi-structured telephone interviews. Quantitative data was analysed using descriptive statistics and qualitative data using thematic analysis. Results: 27 questionnaire responses were received from participants from varied professional backgrounds. The overriding themes from the questionnaires were 'learning from colleagues', 'potential impacts in the workplace', 'challenges of interdisciplinary learning' and 'suggestions for improvement'. 10 telephone interviews were conducted. 2/10 participants said that the interdisciplinary nature of the course significantly affected their decision to enrol on it. 'Social factors', 'course factors' and 'individual factors' emerged as overriding themes from the transcribed interview data. Conclusions: Participants reported being affected in different ways and to different extents by social, individual and course factors related to interdisciplinary learning. These mirror the behavioural, personal and environmental determinants of Bandura's social cognitive theory. Several advantages and disadvantages identified by participants show parallels with adult learning theory and the interprofessional education literature. These results may be used to inform strategies for optimising the experience of participants on future interdisciplinary learning courses.